Finite element modeling of temporal bone graft changes in XLIF: Quantifying biomechanical effects at adjacent levels - Ramakrishna, Vivek A. S.; Chamoli, Uphar; Larosa, Alessandro G.; Mukhopadhyay, Subhas C.; Prusty, B. Gangadhara; Diwan, Ashish D. (Journal of orthopaedic research, 2022)
Extreme lateral interbody fusion allows for the insertion of a large‐footprint interbody cage while maintaining the presence of natural stabilizing ligaments and the facets. It is unclear how the load‐distribution mechanisms through these structures alter with temporal changes in the bone graft. The aim of this study was to examine the effects of temporal bone graft changes on load distribution among the cage, graft, and surrounding spinal structures using finite element analysis. Thoracolumbosacral spine computed tomography data from an asymptomatic male subject were segmented into anatomical regions of interest and digitally stitched to generate a surface mesh of the lumbar spine (L1‐S1). The interbody cage was inserted into the L4‐L5 region during surface meshing. A volumetric mesh was generated and imported into finite element software for pre‐processing, running nonlinear static solves, and post‐processing. Temporal stiffening was simulated in the graft region with unbonded (Soft Callus, Temporal Stages 1–3, Solid Graft) and bonded (Partial Fusion, Full Fusion) contact. In flexion and extension, cage stress reduced by 20% from the soft callus to solid graft state. Force on the graft was directly related to its stiffness, and load‐share between the cage and graft improved with increasing graft stiffness, regardless of whether contact was fused with the endplates. Fused contact between the cage‐graft complex and the adjacent endplates shifted load‐distribution pathways from the ligaments and facets to the implant, however, these changes did not extend to adjacent levels. These results suggest that once complete fusion is achieved, the existing load paths are seemingly diminished.